CUSTOMER LOYALTY IN DIGITAL BANKING: AN INTEGRATED MODEL OF UX, SECURITY, TRUST, AND SATISFACTION - Aditya Ramadhan; Dian Masyita; Elisa Susanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the integrated influence of User Experience (UX), Digital Security, and Trust on Customer Satisfaction and Customer Loyalty within the BYOND BSI mobile banking application, a digital upgrade from the previous Mobile BSI system. Using a quantitative approach and SEM-PLS analysis on 400 respondents, the findings reveal that UX and Digital Security significantly enhance Trust and Satisfaction, which then strongly drive Customer Loyalty. Although BYOND BSI demonstrates adequate performance in usability and security, the results highlight several critical issues users still encounter, including application efficiency, authentication delays, accessibility challenges, and inconsistent customer support responsiveness. Trust also emerges as an essential psychological mediator linking users’ digital experiences with their loyalty intentions. The model fit results confirm strong predictive accuracy, indicating that the integrated model effectively explains loyalty formation in digital banking. Overall, this study provides empirical evidence that continuous improvements in performance stability, adaptive security, reliability, and service support are required to strengthen long-term customer commitment in the era of digital banking transformation.